Discovery of a Potent and Orally Active Dual GPBAR1/CysLT1R Modulator for the Treatment of Metabolic Fatty Liver Disease - Fiorucci, Stefano; Rapacciuolo, Pasquale; Fiorillo, Bianca; Roselli, Rosalinda; Marchianò, Silvia; Di Giorgio, Cristina; Bordoni, Martina; Bellini, Rachele; Cassiano, Chiara; Conflitti, Paolo; Catalanotti, Bruno; Limongelli, Vittorio; et al. (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are two highly prevalent human diseases caused by excessive fat deposition in the liver. While multiple approaches have been suggested, NAFLD/NASH remains an unmet clinical need. Here we report the discovery of a novel class of hybrid molecules designed to function as cysteinyl leukotriene receptor 1 (CysLT1R) antagonists and G protein bile acid receptor 1 (GPBAR1/TGR5) agonists for the treatment of NAFLD/NASH. The most potent of these compounds generated by harnessing the scaffold of previously described CystLT1R antagonists showed efficacy in reversing liver histopathology features in a preclinical model of NASH, reshaping the liver transcriptome and the lipid and energy metabolism in the liver and adipose tissues. In summary, the present study described a novel orally active dual CysLT1R antagonist/GPBAR1 agonist that effectively protects against the development of NAFLD/NASH, showing promise for further development.